Signs in the Night. Effigies et Pilae in the Compitalia - Corre, Nicolas (ARYS. Antigüedad: Religiones y Sociedades, 2023)
In Rome, during the Compitalia, at the beginning of the year, wool artifacts were hung at night at various crossroads, so that the Lares spare the living, contenting themselves with these balls and simulacra. However, the hanging of wool effigies constitutes “un système de pratiques symboliques de communication”, whose originality lies in the manipulation of an image. This ritual is similar in form to a census, but by bringing all the elements together, its meaning is revealed: the hanging of the effigies constitutes the preliminaries of a ceremony comparable to a lustratio, and makes possible the (re)constitution of a community. The nocturnal rite, once considered “magical-superstitious”, is not opposed to the so-called “religious” sacrifice of the day. On the contrary, it complements.